(untitled) - Gabehart, Scott (New York, 2002)
This volume demystifies the valuation process so that people with no prior evaluation experience can realistically estimate the fair market value of almost any company.
Keywords: Business enterprises,Hoạt động kinh doanh; Valuation,Đánh giá; United States,Hoa Kỳ